The accidental apprentice - Foody, Amanda (Foody, Amanda. Wilderlore, 2021)
Eleven-year-old Barclay Thorne yearns for the quiet life of a mushroom farmer, but after unwittingly bonding with a beast in the forbidden Woods, he must seek Lore Keepers to break the bond and return home.